Stimulation of a Gs-like G protein in the osteoclast inhibits bone resorption but enhances tartrate-resistant acid phosphatase secretion. - Moonga, B; Pazianas, M; Alam, A; Shankar, V; Huang, C; Zaidi, M (1993)
Previous studies have demonstrated that G-protein agonists induce quiescence (Q effect) or retraction (R effect) in isolated osteoclasts. We now report the functional effects of such agonists on osteoclastic bone resorption and enzyme release. Exposure of osteoclasts to tetrafluoro-aluminate anions (AlF4-), a universal G protein stimulator, resulted in a marked concentration-dependent inhibition of bone resorption. This was associated with a dramatic increase in the secretion of the osteoclast-specific enzyme, tartrate-resistant acid phosphatase (TRAP). Cholera toxin, a Gs stimulator and a selective Q effect agonist, similarly abolished bone resorption and enhanced TRAP secretion. In contrast, pertussis toxin, a Gi inhibitor and a selective R effect agonist, inhibited bone resorption significantly, but slightly reduced enzyme release. The results suggest an involvement of a Gs-like G protein in TRAP secretion from the osteoclast, possibly through a cyclic AMP-dependent mechanism.